Intraoperative magnetic resonance imaging versus standard neuronavigation for the neurosurgical treatment of glioblastoma: A randomized controlled trial - Kubben, Pieter L. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Although the added value of increasing extent of glioblastoma resection is still debated, multiple technologies can assist neurosurgeons in attempting to achieve this goal. Intraoperative magnetic resonance imaging (iMRI) might be helpful in this context, but to date only one randomized trial exists. METHODS: We included 14 adults with a supratentorial tumor suspect for glioblastoma and an indication for gross total resection in this randomized controlled trial of which the interim analysis is presented here. Participants were assigned to either ultra-low-field strength iMRI-guided surgery (0.15 Tesla) or to conventional neuronavigation-guided surgery (cNN). Primary endpoint was residual tumor volume (RTV) percentage. Secondary endpoints were clinical performance, health-related quality of life (HRQOL) and survival. RESULTS: Median RTV in the cNN group is 6.5% with an interquartile range of 2.5-14.75%. Median RTV in the iMRI group is 13% with an interquartile range of 3.75-27.75%. A Mann-Whitney test showed no statistically significant difference between these groups (P =0.28). Median survival in the cNN group is 472 days, with an interquartile range of 244-619 days. Median survival in the iMRI group is 396 days, with an interquartile range of 191-599 days (P =0.81). Clinical performance did not differ either. For HRQOL only descriptive statistics were applied due to a limited sample size. CONCLUSION: This interim analysis of a randomized trial on iMRI-guided glioblastoma resection compared with cNN-guided glioblastoma resection does not show an advantage with respect to extent of resection, clinical performance, and survival for the iMRI group. Ultra-low-field strength iMRI does not seem to be cost-effective compared with cNN, although the lack of a valid endpoint for neurosurgical studies evaluating extent of glioblastoma resection is a limitation of our study and previous volumetry-based studies on this topic.